Factors influencing adherence to dietary recommendations for type 2 diabetes mellitus and their impact on disease control: A cross-sectional study - Harsh K. Patel; Sumit V. Unadkat; Bela A. Patel; Dipesh V. Parmar (Journal of Family Medicine and Primary Care)
Background and Objectives: Diabetes is a chronic metabolic disease, with current estimates by the IDF (International Diabetes Federation) suggesting nationwide prevalence rates of 9.2% among Indians aged 20–79 years. An appropriate dietary pattern is widely accepted as a cornerstone of treatment among diabetes patients. However, motivating patients to achieve dietary self-care behaviors is challenging and requires ongoing efforts between patients and multidisciplinary teams. Therefore, the objectives of this study were to assess the level of adherence to the diet, to find out the association between dietary practices and disease profile, and to explore the reasons behind not adhering to the recommended diet. Methodology: The present cross-sectional study was conducted among type 2 diabetic patients visiting the NCD clinic in a tertiary care hospital and three CHCs in Jamnagar district. The final sample size was 450. A structured interview schedule containing sociodemographic profiles, details regarding diabetes mellitus, and dietary details was developed. Dietary assessment was done using the UKDDQ. Result: In a study of 450 participants, 44.88% were aged 61–70 years. The majority were Hindu (88%), with 69.3% residing in urban areas and 30.7% in rural areas. Using the UKDDQ dietary score, 71.55% had a healthy diet. This score was negatively correlated with BMI, HbA1c, and RBS. Factors such as family type, area of residence, family history of diabetes mellitus, duration of diabetes, mode of treatment, HbA1c, and complications of diabetes were significantly associated with the dietary score. Conclusion: The study found that poor dietary scores were linked to worse disease outcomes in type 2 diabetes. Identifying and addressing barriers to dietary adherence is crucial for improving outcomes and modifying recommendations accordingly.